Dentoalveolar mandibular changes with self-ligating versus conventional bracket systems: A CBCT and dental cast study - Marcio Rodrigues de Almeida; Cristina Futagami; Ana Cláudia de Castro Ferreira Conti; Paula Vanessa Pedron Oltramari-Navarro; Ricardo de Lima Navarro (Dental Press Editora, 2015)
OBJECTIVE: The aim of the present study was to compare dentoalveolar changes in mandibular arch, regarding transversal measures and buccal bone thickness, in patients undergoing the initial phase of orthodontic treatment with self-ligating or conventional bracket systems. METHODS: A sample of 25 patients requiring orthodontic treatment was assessed based on the bracket type. Group 1 comprised 13 patients bonded with 0.022-in self-ligating brackets (SLB). Group 2 included 12 patients bonded with 0.022-in conventional brackets (CLB). Cone-beam computed tomography (CBCT) scans and a 3D program (Dolphin) assessed changes in transversal width of buccal bone (TWBB) and buccal bone thickness (BBT) before (T1) and 7 months after treatment onset (T2). Measurements on dental casts were performed using a digital caliper. Differences between and within groups were analyzed by Student's t-test; Pearson correlation coefficient was also calculated. RESULTS: Significant mandibular expansion was observed for both groups; however, no significant differences were found between groups. There was significant decrease in mandibular buccal bone thickness and transversal width of buccal bone in both groups. There was no significant correlation between buccal bone thickness and dental arch expansion. CONCLUSIONS: There were no significant differences between self-ligating brackets and conventional brackets systems regarding mandibular arch expansion and changes in buccal bone thickness or transversal width of buccal bone.